Start-up, adjustment and long-term performance of a two-stage bioremediation process, treating real acid mine drainage, coupled with biosynthesis of ZnS nanoparticles and ZnS/TiO2 nanocomposites - Vitor, G. (2016)
Acid mine drainage (AMD) generation is a widespread environmental problem in Europe, including Portugal. Previous experience has shown that a combined process consisting of an anaerobic sulphate-reducing bioreactor, following neutralization with calcite tailing, produces water complying with legal irrigation requirements from synthetic AMD. Aiming the treatment of real AMD a new bioreactor was inoculated with a SRB enrichment obtained from sludge from a local WWTP anaerobic lagoon. In the initial batch phase, sulphate supplementation was needed to achieve high sulphate-reducing bacteria counts before continuous feeding of AMD was started. The system quickly achieved good performance, proving it is easy to start-up. However, this time the neutralization step failed to keep bioreactor affluent pH higher than 5 for longer than three weeks. This was due to armouring of calcite by precipitates of various metals present in AMD. A new configuration, replacing a packed-bed column by a shallow contact basin, proved to be more robust, avoiding clogging, short-circuiting and providing long-term neutralization. The treated effluent, with excess of biologically generated sulphide, was successfully used to synthesize zinc sulphide nanoparticles, both in pure form and as a ZnS/TiO2 nanocomposite, thus proving the feasibility of coupling an AMD bioremediation system with the synthesis of metal sulphide nanoparticles and nanocomposites.